Glutamate-based Therapies for Psychiatric Disorders - Skolnick, Phil.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2010)
Both metabotropic and ionotropic glutamate receptors present attractive “druggable” targets in treating disorders of the central nervous system. There has been a dramatic shift in the focus of glutamate-based therapies away from neurologic disorders such as stroke and traumatic brain injury to the treatment of psychiatric disorders. This “Milestones in Drug Therapy” volume offers a unique, contemporary overview of preclinical and clinical evidence that modulating glutamatergic tone is an effective means of treating psychiatric disorders ranging from depression and anxiety to schizophrenia and drug abuse. The ability to treat diseases such as depression and schizophrenia through multiple, glutamate-based mechanisms offers a unique therapeutic opportunity, as described in this book.
N-Methyl-d-Aspartate (NMDA) Antagonists for the Treatment of Depression -- Ionic Glutamate Modulators in Depression (Zinc, Magnesium) -- Positive Allosteric Modulation of AMPA Receptors: A Novel Potential Antidepressant Therapy -- Glutamatergic Modulators for the Treatment of Major Depressive Disorder: Metabotropic Glutamate Receptors -- Positive Modulation of AMPA Receptors as a Broad-Spectrum Strategy for Treating Neuropsychiatric Disorders -- Activation of Group II Metabotropic Glutamate Receptors (mGluR2 and mGluR3) as a Novel Approach for Treatment of Schizophrenia -- mGluR1 Negative Allosteric Modulators: An Alternative Metabotropic Approach for the Treatment of Schizophrenia -- Metabotropic Glutamate Receptors as Targets for the Treatment of Drug and Alcohol Dependence -- Metabotropic Approaches to Anxiety.
Keywords: Psychopharmacology; Pharmacology; Psychiatry; Neurosciences; Psychopharmacology; Pharmacology/Toxicology.; Psychiatry; Neurosciences